Responses to analogues of growth hormone-releasing hormone in normal subjects, and in growth-hormone deficient children and young adults. - Grossman, A; Savage, M; Lytras, N; Preece, M; Sueiras-Diaz, J; Coy, D; Rees, L; Besser, G (1984)
Three analogues of growth hormone-releasing hormone (GHRH) have been compared in normal subjects. GHRH(1-29)NH2 is equipotent to GHRH(1-40); increasing doses from 10-200 micrograms per subject augments the duration of stimulated growth hormone (GH) release, but the peak serum GH shows only a poor correlation with dose. The derivative D-Ala2-GHRH(1-29)NH2 is no more potent than the unsubstituted GHRH(1-29)NH2. In 20 children and young adults with growth hormone deficiency by conventional criteria, eight showed normal or only slightly subnormal peak serum GH responses to GHRH(1-40) or GHRH(1-29)NH2. These included two patients with tumours of the hypothalamus, as well as six with idiopathic isolated growth hormone deficiency or panhypopituitarism. A poor response to GHRH was generally seen in patients on long-term GH therapy. Priming with GHRH, in either a single bolus or a continuous infusion, did not increase the GH response to GHRH. It is concluded that GHRH(1-29)NH2 is a useful analogue in the testing of GH reserve in patients with growth hormone deficiency, and has considerable potential for long-term therapy.